2021
DOI: 10.1007/s00787-021-01798-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors explain a significant part of associations between adolescent well-being and the social environment

Abstract: Socio-environmental factors play an important role in adolescent well-being, but potential genetic contributions to these associations are rarely assessed. To address this gap in the literature, associations between well-being and family conflict and functioning, number of friends, friendship importance and satisfaction, and leisure time variables were studied in N =  ~ 4700 twin pairs from the Netherlands Twin Register, us ing generalized estimating equations and twin-difference scores. When twin-difference s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…While these associations were described in the general population, our results suggest that these patterns remain in individuals with SUD. Moreover, our findings showed that the genetic liability for well-being is associated with better outcomes, namely lower rates of outpatient treatments and fewer problems related to family and social relationships, which is consistent with the role of the genetics underlying well-being in healthy family relationships [58].…”
Section: Discussionsupporting
confidence: 88%
“…While these associations were described in the general population, our results suggest that these patterns remain in individuals with SUD. Moreover, our findings showed that the genetic liability for well-being is associated with better outcomes, namely lower rates of outpatient treatments and fewer problems related to family and social relationships, which is consistent with the role of the genetics underlying well-being in healthy family relationships [58].…”
Section: Discussionsupporting
confidence: 88%